Characterization and fractionation of SARS-CoV-2 specific IgG from COVID-19 convalescent and post-vaccine group - Purwati; Nora Ertanti; Deya Karsari; Aristika Dinaryanti; Eryk Hendrianto; Igo Syaiful Ihsan; Asa Ardiana; Nanis Nurdiyati; Adita Ayu Permanasari; Bagus Satrio Nurwito; Andang Miatmoko (Bali medical journal, 2025)
Purpose: This study aimed to explore the method for characterization and fractionation of SARS-CoV-2 IgG specific from convalescent COVID-19 patients, post-inactive, and post-mRNA vaccines Patients and methods: The procedures include blood sample collection, SARS-CoV-2 specific IgG content screening, IgG fractionation, and validate specific IgG. Statistical analysis was carried out to evaluate the significance value of SARS-CoV-2 IgG presence in each sample group. Results: The results showed that the post-mRNA vaccine samples had the highest levels of SARS-CoV-2 IgG antibodies. Furthermore, the validation was confirmed to be specific to SARS-CoV-2 IgG, as indicated by the heavy and light chains marked at ~50kDa and 25kDa, respectively. Conclusion: A significant difference between the SARS-CoV-2 IgG content between the three sample groups is indicated by a P value of 0.0043.